Low-power on-chip communication based on transition-aware global signaling (TAGS). - Kaul, H. (IEEE Transactions on VLSI systems)
In this paper, we propose a new circuit structure, the transition aware global signaling (TAGS) receiver, that detects transitions at arbitrary switch points. The major performance advantage of this circuit occurs when it switches before the 50% point in the input transition. The TAGS receiver stores the next state of the line while quiet. Upon detection of a transition at the end of the line the output is temporarily driven by the stored next state. Transitions at the output of the receiver are much faster than at the end of the line since they are generated locally. Its ability to detect transitions before a standard inverter and locally generate them at its output, allows its use at the end of long interconnects with fewer repeaters for the same delay as the standard repeater paradigm. The need for fewer repeaters with the TAGS scheme results in lower power consumption for on-chip global communication, while also reducing the placement overhead involved with large buffer blocks. This is shown in the context of bus optimizations, where TAGS achieves up to 50% reduction in power compared to standard repeaters. In an industrial 0.13-μm CMOS process, TAGS receivers enable 8-mm-long buses at 1.5-GHz clock rates without repeaters, while the traditional scheme required three repeaters on the line. An extensive analysis of crosstalk noise in the bus environment shows that TAGS can handle the noise levels produced in typical bus structures. Also, the variation of delay in the bus structure under worst-case power supply noise for the TAGS scheme is typically smaller than the delay variation using the standard repeater scheme.